FATWA PEMBIAYAAN PENGURUSAN HAJI DAN PENERAPAN PRODUKNYA - Hasanudin Hasanudin (Islamic Economics and Business Faculty of UIN Antasari, 2015)
Abstract: This paper discusses the fatwa from DSN-MUI about the maintenance of the Hajj using twocontract, namely Ijara as the main contract and qardh the form of bailout funds pilgrimage (if re-quired); between funds qardh with ujrah there should be no taaluq; and these in line with the fatwacouncil hisbah Exactly. The question by the community is the practice of financing the maintenance ofthe Hajj by a number of Islamic banks. Of this paper can be concluded that the financing arrangementpilgrimage serves as Kasab/initiative/effort for financing receiver pilgrimage of Islamic Financial Insti-tutions. Method of payment on the debt qardh Taqsith considered more easy than by saving. Through-out not used negatively, financing the maintenance of pilgrimage by Islamic Financial Institutions arenot contrary to the concept of fi istithaah there al-hajj.